Association among cytokine profiles of innate and adaptive immune responses and clinical-virological features in untreated patients with chronic hepatitis B - Gu, Yurong (BMC Infect Dis, 2020)
BACKGROUND: Complete clearance of intracellular viruses depends on effector cells of innate and adaptive immune systems. This study aimed to identify the relationships among antiviral cytokines produced by natural killer (NK) and T cells and clinical-virological characteristics in untreated chronic hepatitis B (CHB) patients. METHODS: We measured antiviral cytokines interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), and interleukin-2 (IL-2) produced by T, NK and natural killer T (NKT) cells, respectively, in a cohort with chronic hepatitis B virus (HBV) infection (CHB). We also correlated these cytokines with clinical-virological characteristics using a linear regression model. RESULTS: levels of IFN-γ(+) and TNF-α(+) CD4(+) and CD8(+) T cells were significantly higher in immune active (IA) phase than in other phases. Immune tolerant (IT) patients showed the lowest expression of IFN-γ by NK and NKT cells, and TNF-α by NK cells. IFN-γ(+), TNF-α(+) and IL-2(+) CD4(+) and CD8(+) T cells frequencies were similar between IA and gray zone (GZ) phases. Principal component analysis based on cytokines confirmed that most IT patients significantly differed from inactive carriers (IC) and IA patients, while GZ patients were widely scattered. Multivariate analysis showed both T and NK cells producing IFN-γ and TNF-α, but not IL-2, had significant association with serum alanine aminotransferase (ALT). Moreover, IFN-γ(+) NKT cells were associated with HBV DNA, while IFN-γ(+) CD4(+) and CD8(+) T cells were correlated with age. CONCLUSION: HBV clinical phases are characterized by distinct cytokine signatures, which showed relationship to viral features in these untreated CHB patients.